MHC2TA promoter polymorphism (-168*G/A, rs3087456) is not associated with susceptibility to rheumatoid arthritis in British Caucasian rheumatoid arthritis patients. - Harrison, P; Pointon, J; Farrar, C; Harin, A; Wordsworth, B (2007)
OBJECTIVE: To investigate the association of a single-nucleotide polymorphism (SNP) in the promoter region of MHC2TA gene (-168*G/A, rs3087456), which has previously been described in a Swedish rheumatoid arthritis (RA) cohort, in British Caucasian RA patients. METHODS: We genotyped 733 RA patients and 613 healthy controls for MHC2TA -168*G/A SNP by amplification-refractory mutation system (ARMS). Data were analysed using SPSS version 13.0 software and the chi-square test was applied where appropriate. RESULTS: The MHC2TA -168*G/A SNP was not associated with increased susceptibility to RA in our patients. Stratifying the patients according to the presence or absence of rheumatoid factor (RF) showed the SNP to be more common in RF negative patients, but this did not reach statistical significance. CONCLUSION: We did not confirm the previously reported association of this MHC2TA polymorphism with RA in our UK population despite its ethnic similarities with the Swedish population in which it was first described.